Natural Ingredients of Beans as Growth Medium and Propagation of Endophytic Bacteria from Lowland Eggplant - Arika Purnawati; Safira Rizka Lestari; Iis Purnamawati (Nusantara Science and Technology Proceedings, 2022)
Endophytic bacteria are defined as a group of microbes that live in plant tissues that do not cause disease and are mutually related to the host plant, can be isolated from all parts of the plant were roots, stems, leaves, and seeds. Endophytic bacteria have the potential to produce natural products for agriculture, increase plant growth, and support the sustainable development of agriculture. The growth of endophytic bacteria in vitro generally uses a medium that contains nutrients including macronutrients, namely elements (C, H, O, and N), micronutrients, namely non-metallic elements (S and P), metallic elements (Ca, Zn, Na, K, Cu). , Mn, Mg, and Fe), vitamins, water, and energy. To meet these growth requirements, currently the growth and propagation of endophytic bacteria generally still use synthetic media which are expensive and in the field, mainly by farmers, are not easy to obtain. The study aimed to obtain an alternative medium made from beans for the growth and propagation of endophytic bacteria from lowland eggplants. The types of beans were soybeans, green beans, red beans, cowpeas, peanuts, and Nutrient Agar (NA) as control. Inoculation into the medium was done using the spread plate technique. This technique is preceded by a dilution and at dilution of 10-7 was taken 0.1 ml then to be spread on the growing medium. Observations were growing and colony counting was done 24 hours after inoculation. The results were: (1) endophytic bacteria from lowland eggplant can grow well on all mediums with the best growth on NA medium, (2) all media can be used as the propagation of endophytic bacteria from lowland eggplant plants, (3) the assumed of the growth curve is logarithmic with 4 phases were lag phase, exponential phase, stationer phase, death phase.